2022
DOI: 10.3389/fonc.2022.882018
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and BP neural network revealed abnormal B cell infiltration predicts the survival of lung cancer patients

Abstract: FAM83A gene is related to the invasion and metastasis of various tumors. However, the abnormal immune cell infiltration associated with the gene is poorly understood in the pathogenesis and prognosis of NSCLC. Based on the TCGA and GEO databases, we used COX regression and machine learning algorithms (CIBERSORT, random forest, and back propagation neural network) to study the prognostic value of FAM83A and immune infiltration characteristics in NSCLC. High FAM83A expression was significantly associated with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Using ssGSEA by interrogating the expression levels of reported specific genes of adaptive and innate immune cell types, we computed the infiltration levels of 28 immune cell types per sample. Next, we integrated Lasso and RF algorithms to obtain key immune cell types from 28 immune cell types [50]. Lasso and RF were constructed under 10-fold cross-validation, and the setting parameters of RF were 800 decision trees.…”
Section: Evaluation Of Immune Cell Characteristics In Hf Via Ssgsea A...mentioning
confidence: 99%
“…Using ssGSEA by interrogating the expression levels of reported specific genes of adaptive and innate immune cell types, we computed the infiltration levels of 28 immune cell types per sample. Next, we integrated Lasso and RF algorithms to obtain key immune cell types from 28 immune cell types [50]. Lasso and RF were constructed under 10-fold cross-validation, and the setting parameters of RF were 800 decision trees.…”
Section: Evaluation Of Immune Cell Characteristics In Hf Via Ssgsea A...mentioning
confidence: 99%
“…The investigation showed that FAM83A presents prognostic and predictive properties supported by machine-learning algorithms. Therefore, the unusual tumor permeation of naive B cells monitored by FAM83A may reveal robust biomarkers that preview the clinical behavior of patients with non-small cell lung cancer (10).…”
mentioning
confidence: 99%